Zinc supplementation in children with asthma exacerbation - Sanguansak Rerksuppaphol; Lakkana Rerksuppaphol (MDPI AG, 2016)
Zinc deficiency has demonstrated an association with the risk of asthma. This study aimed to evaluate the efficacy of zinc supplementation in reducing the severity of childhood asthma exacerbation. A number of 42 children with asthma exacerbation admitted to the hospital were randomized to receive either zinc bis-glycinate (30 mg elemental zinc/day) or a placebo in adjuvant to the standard treatment. The pediatric respiratory assessment measure (PRAM) was used to measure the asthma severity. The primary outcome was a change in asthma severity from the baseline to the end of study. The study found that PRAM score in the zinc group showed a more rapid decrease compared to the control group at the 24-hour (2.2±1.3 vs. 1.2±1.3; P=0.015) and 48-hour (3.4±2.0 vs. 2.2±1.8; P=0.042) intervals. At admission, overall mean serum zinc level was 63.8 mg/dL and 57.1% of children had zinc deficiency with no difference in prevalence between groups. PRAM scores did not differ between children with low and normal zinc status. In conclusion, zinc supplementation as the adjuvant therapy to the standard treatment during asthma exacerbation resulted in rapid lessening of severity.